Кавітаційне очищення стічних вод жиркомбінату від органічних забруднень у присутності газів різної природи - Вашкурак, У. Ю.; Шевчук, Л. І.; Vashkurak, U. Yu.; Shevchuk, L. I. (Lviv Politechnic Publishing House, 2018)
Досліджено вплив газів різної природи в кавітаційних умовах і без них на руйнування органічних забруднень, які містяться в стічних водах жиркомбінату, а саме вплив азоту, кисню, повітря, суміші азоту і кисню в співвідношенні 1:1. Встановлено, що ефективність спільного застосування ультразвуку і газу, незалежно від його природи, є вищою, ніж барботування самого лише газу. Найвищого ступеня очищення стічних вод жиркомбінату досягнуто за спільної дії ультразвуку та повітря. Розраховано ступені руйнування органічних речовин, які підтверджують доцільність спільного застосуванн ультразвуку з повітрям.

The influence of the gases of the different nature in cavitational conditions and without them on the destruction of organic contaminants which contained in wastewater of oil – fat factory was investigated, namely the influence of nitrogen, oxygen, air, a mixture of nitrogen and oxygen in the ration 1: 1. It has been established that the efficiency of the common uses of ultrasound and gas, regardless of its nature, is higher than the bubbling of the gas alone. The highest degree of water tretment oil – fat factory was achieved with the common action of ultrasound with air. The calculation of the degree of destruction of organic substances were carried out, which confirm the expediency of the common action of ultrasound with air.
Cavitation wastewater treatment of oil-fat factory from organic contamination in the presence of the gases of different nature
Keywords: кавітація; жиркомбінат; стічні води; органічні забруднення; гази різної природи; cavitation; oil – fat factory; wastewater; organic pollution; gases of different nature